EFEKTIVITAS EKSTRAK DAUN BELIMBING WULUH (Averrhoa bilimbi L.) SECARA TOPIKAL TERHADAP PENYEMBUHAN LUKA PADA KELINCI (Oryctolagus cuniculus) - Richa Dwi Novita Sari; Antonius Budiawan; Angga Rahabistara Sumadji (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2023)
Wound healing is a repair process of damaged skin tissue caused by injury. The bilimbi (Averrhoa bilimbi L.) plant is widely known to have potential in wound healing and the plant part that is commonly used is the leaves. The purpose of this study was to determine the wound healing effects of bilimbi leaf extract (Averrhoa bilimbi L.) on rabbits (Oryctolagus cuniculus) topically. The wound healing test was conducted using the New Zealand strain rabbit test animal. The rabbit’s back skin was induced with 8 mm diameter wound and the induced wounds were grouped into 5 groups. The groups included a negative control group that was given with aqua dest solution; the positive control group was given with betadine solution; treatment groups were given with 3%; 6%; and 12% bilimbi leaves extract. The wounds that were treated with betadine solution and bilimbi leaves extract 3% healed on day 13th. The wounds that were treated with bilimbi leaves extract 6 and 12% were healed on day 12nd. The different results showed by the wounds that were treated with aqua destilata which were healed on day 14th. The results showed that bilimbi leaf extract was topically effective in wound healing on rabbit test animals. The most effective concentration of bilimbi leaves extract in wound healing was 6% and 12%.